A Method Enabling Comprehensive Isolation of Arabidopsis Mutants Exhibiting Unusual Root Mechanical Behavior - Tojo, Hiroshi; Nakamura, Aki; Ferjani, Ali; Kazama, Yusuke; Abe, Tomoko; Iida, Hidetoshi (Frontiers in Plant Science, 2021)
Root penetration into soils is fundamental for land plants to support their own aboveground parts and forage water and nutrients. To elucidate the molecular mechanisms underlying root mechanical penetration, mutants defective in this behavior need to be comprehensively isolated; however, established methods are currently scarce. We herein report a method to screen for these mutants of Arabidopsis thaliana and present their phenotypes. We isolated five mutants using this method, tentatively named creep1 to creep5, the primary roots of which crept over the surface of horizontal hard medium that hampered penetration by the primary root of the wild type, thereby forcing it to spring up on the surface and die. By examining root skewing, which is induced by a touch stimulation that is generated as the primary roots grow along a vertical impenetrable surface, the five creep mutants were subdivided into three groups. While the majority of wild-type primary roots skewed slightly leftward, nearly half of the primary roots of creep1 and creep5 skewed rightward as viewed from above. The primary roots of creep4 displayed scattered growth, while those of creep2 and creep3 showed a similar phenotype to the wild-type primary roots. These results demonstrate the potential of the method developed herein to isolate various mutants that will be useful for investigating root mechanical behavior regulation not only in Arabidopsis, but also in major crops with economical value.